The Impact of Social Media Use on Job Burnout: The Role of Social Comparison - Han, Ruixia; Xu, Jian; Ge, Yan; Qin, Yulin (Frontiers in Public Health, 2020)
Through an online survey of a working population sample (N = 530), this study examines the role of social comparison between social media use and job burnout. The results show that: (1) there is a significant positive correlation between social media use and job burnout; (2) social comparison plays a moderating role in social media’s impact on burnout. In high social comparative groups, the moderating role develops into an mediating role, which means that job burnout is only significant when social media addiction and the inclination of social comparison are simultaneously strong; (3) Social media users who often make downward comparison and get positive emotions from it are more prone to job burnout. This study reveals the possible negative effects of overuse of new media and enriches the understanding of how social media shapes individuals' psychology and behavior. Studies have also shown that regulating and controlling social comparisons and avoiding excessive use of social media may be effective in reducing job burnout.